Could The Irish Miracle Be Repeated in Hungary? - Zoltán J. Ács; Colm O'Gorman; Laszlo Szerb; Siri Terjesen (Max Planck Institute of Economics, 2006)
It is widely recognized that foreign direct investment (FDI) plays an important role in economic development. Internationalization theory is used to explore how inward FDI impacts entrepreneurial activity. Using data from the Global Entrepreneurship Monitor we find significant differences in entrepreneurial activity between Ireland and Hungary in both the type of people starting businesses and the opportunities pursued. These results suggest that economic development policies for middle-income countries, like Hungary, should focus on increasing human capital, promote enterprise development, and upgrading the quality of FDI.
Older version: http://hdl.handle.net/10419/24893
Keywords: M13; F23; O10; O30; 330; Entrepreneurial Activity; GEM; Economic Development; Entrepreneurs; Foreign Direct Investment; Knowledge Spillovers; Ireland; Hungary; Auslandsinvestition; Wissenstransfer; Entwicklung; Entrepreneurship-Ansatz; Vergleich; Irland; Ungarn